1994
DOI: 10.1002/bsl.2370120207
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of civil justice: The litigation crisis attitudes of civil jurors

Abstract: Public perceptions that the civil justice system is in crisis are apparently widespread, but little is known about the causes or correlates of such views. This article analyzes the litigation crisis attitudes of a sample of civil jurors. Like the public, jurors endorsed a number of statements suggesting that there is a litigation crisis. Factor analysis identified two independent components: general concern over excessive litigation, and criticism of the civil jury. Litigation crisis views were found in all de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…A variable entitled Political Efficacy was formed by combining responses to two items used in prior research on political efficacy, or the extent to which people think political change is possible through the efforts of its citizens (Acock & Clark, 1990;Campbell, Gurin & Miller, 1954;Hans & Lofquist, 1994) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variable entitled Political Efficacy was formed by combining responses to two items used in prior research on political efficacy, or the extent to which people think political change is possible through the efforts of its citizens (Acock & Clark, 1990;Campbell, Gurin & Miller, 1954;Hans & Lofquist, 1994) …”
Section: Discussionmentioning
confidence: 99%
“…In prior research (Hans & Lofquist, 1994) civil jurors who scored high in political efficacy were also more supportive of the civil litigation system. That relationship is replicated in this data set.…”
Section: Experience With the Justice Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This juror skepticism about personal injury claims extends beyond medical malpractice cases. Hans and Lofquist [14,15] conducted interviews with jurors in a large study of cases involving individuals with claims against businesses and health provider defendants. They found that jurors often penalized plaintiffs who did not meet high standards of credibility and behavior, including those who did not appear as injured as they claimed, those with preexisting medical conditions, and those who did not do enough to help themselves recover from their injuries.…”
Section: Juror Skepticism About Lawsuitsmentioning
confidence: 99%
“…The strongest relationship was with an attitude scale, the Litigation Crisis Scale, which measured the extent to which a juror believed that there was a litigation crisis and a substantial amount of frivolous litigation (see Hans 2000;Hans and Lofquist 1994). Jurors who showed the greatest suspicion of experts also tended to believe that there were many illegitimate lawsuits.…”
Section: Analysis Questionnaire Responsesmentioning
confidence: 99%